Chinese Competition and Skill-Upgrading in European Textiles: Firm-level Evidence - Ph. Monfort; Hylke Vandenbussche; E. Forlani (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
In this paper we study the effect of import competition from China on the Belgian textiles sector. Our analysis comprises both trade data and firm-level data. We study the evolution of the unit values in textiles exported from China into the EU versus textiles exported from Belgium to the rest of the EU over the past ten years. We clearly find evidence of a widening price gap between Chinese and Belgian textiles export prices. Chinese textiles seem to become relatively cheaper over time. These findings are in line with Schott (2004; 2007) who argues that capital abundant countries in the US and Europe use their endowment advantage to produce product varieties that are superior in quality compared to labour intensive countries like China. Next we use firm-level data on Belgian textiles firms in search of evidence of quality and skill upgrading in Belgian textiles exports. We study the evolution of firm-level variables such as R&D outlays, the proportion of skilled and unskilled labour used in production and capital intensity. Both China's entry into the WTO and the end of the Multi- Fibre Agreement significantly seem to cause important shifts in firm level production processes. A very robust result that emerges from the analysis is the one of skill upgrading. While over the past ten years total employment in the Belgian textiles sector has substantially decreased, the ratio of skilled versus unskilled workers has gone up significantly. The evidence is indicative that the Belgian textile sector has been undergoing substantial changes. It is becoming smaller but at the same time seems to be responding to the competition from a low-wage country like China by increasing the skill-content of its products and moving up the quality ladder.
Keywords: 330; Textilindustrie; Internationaler Wettbewerb; WTO-Beitritt; China; Belgien